TRANSLATION PECULIARITIES OF LAW TERMS (Modern education and development, 2024)
This thesis explores the unique challenges faced by translators working within legal contexts, including issues of equivalence, cultural differences, and the impact of legal systems on translation practices, the role of technology and resources available to legal translators, the importance of context in interpreting legal texts, strategies for effective legal translation.